Factors predictive of the need for renal replacement therapy in critically ill patients with rhabdomyolysis and their outcome - Wei, Tan Chee (2020)
In rhabdomyolysis, the most serious systemic complication is acute kidney injury (AKI), which is associated with the need for renal replacement therapy (RRT) and poor outcome. To identify the factors predictive of the need for RRT in critically ill patients with rhabdomyolysis and their outcome.This was a prospective observational study conducted in the intensive care unit (ICU) of the Hospital Universiti Sains Malaysia over a 1 year period. Consecutive adult patients admitted to the ICU who fulfilled the criteria of rhabdomyolysis at any point during their ICU stay were recruited. Obvious cases of renal failure and pre-existing use of RRT were excluded. Data on factors that are known to predict the need for RRT were recruited. The end point of the study was initiation of RRT during the ICU stay and the outcome. Univariate analysis was performed to identify the factors that were significantly associated with the initiation of RRT. A total of 30 subjects fulfilled the study criteria, of which 4 (13.3%) of them required RRT and 3 (10.0%) death reported. The subject’s APACHE II and SOFA median scores were 9.0 (IQR=14.0) and 3.5 (IQR=6.3), respectively. Majority of the rhabdomyolysis patients 28 (93.3%) were due to trauma. Factors that showed significant association with RRT include SOFA score (P=0.021), peak serum creatine kinase level (P=0.026), peak serum creatinine level (P=0.024), use of sodium bicarbonate (P=0.037), and length of ICU stay (P=0.026). In this study, higher SOFA, peak CK level, peak creatinine level, use of sodium bicarbonate and longer length of stay ICU were the predictive factors leading to initiation of RRT in critically ill patients.